Local Varieties of Cassava: Conservation, Cultivation and Use in Uganda - Nakabonge, Grace; Samukoya, C.; Baguma, Y. (Environment, Development and Sustainability, 2018)
The study explored the theory that on-farm conservation of cassava germplasm is influenced by farmers’ traditional and cultural preferences of particular varieties. Traditional knowledge practices that are used for on-farm conservation of cassava germplasm as well as cassava attributes for selection were assessed. The findings obtained from the study indicated that farmers use traditional knowledge to select and preserve cassava germplasm for future use. It was also clear that farmers have their preferences such as culinary attributes, storability in the ground, early maturity and cooking quality to mention but a few that influence the decisions taken to retain or abandon cultivation of varieties. Therefore, by planting varieties in multiples plots, replanting immediately after harvesting, sharing with others in the community and planting disease-free materials, farmers ensure that they preserve varieties of interest for decades. The information generated during this study could inform development policies tailored toward ensuring sustainable on-farm conservation of cassava genetic resources.
Keywords: On farm , Socio-cultural , Germplasm , Traditional farmer knowledge